Palm heart harvesting in the Brazilian Atlantic forest: changes in industry structure and the illegal trade - Galetti, M.; Fernandez, J. C. (Blackwell Science, 1998)
1. Until the late 1960s, Euterpe edulis was the most important edible palm species in the Brazilian markets. Since then, overharvesting of natural stands and the limited scope of plantations have caused the industry to shift to the multistemmed E, oleracea from the Amazon river estuary.2, As a result of the relocation of the industry, the structure of the palm harvesting industry has changed and illegal trade has continued to exploit the remaining natural stands of E, edulis.3, it is suggested that, to avoid the total harvesting of E. edulis and to achieve sustainable management of the palm heart, it will be necessary to diversify the local economy, create incentives for small land owners to improve their management practices, while keeping their competitiveness against the illegal trade, create the incentive of new sources of palm hearts and create a 'green stamping' For management palms.4, Transformation of the illegal structure of the palm heart industry is probably the only solution to avoid the total depletion of the wild stands of E. edulis.
Keywords: Amazon forest; Euterpe edulis; frugivores; keystone species; sustainable management